Comparing Distributions: The Harmonic Mass Index - Jeroen Hinloopen; Charles van Marrewijk (Tinbergen Institute, 2005)
The information contained in PP-plots is transformed into a single number. The resulting Harmonic Mass (HM) index is distribution free and its sample counterpart is shown to be consistent. For a wide class of CDFs the exact analytical expression of the distribution of the sample HM index is derived, assuming the two underlying samples to be drawn from the same distribution. The robustness of the concomitant test statistic is assessed, and four different methods are discussed for applying the HM test in case of asymmetric samples.
Keywords: C12; C14; 330; Distribution; PP-plot; test statistic; critical percentile values; robustness.